2006
DOI: 10.1007/s10530-005-4205-2
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Stochasticity, Environmental Variability, and Windows of Invasion Risk for Bythotrephes Longimanus in North America

Abstract: Biological invasions are a leading threat to freshwater biodiversity worldwide. A central unanswered question of invasion ecology is why some introduced populations establish while most fail. Answering this question will allow resource managers to increase the specificity and effectiveness of control efforts and policy. We studied the establishment of spiny water flea (Bythotrephes longimanus) in the United States and Canada by modeling introduction failure caused by demographic stochasticity, environmental va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 67 publications
3
34
1
Order By: Relevance
“…Niche availability, indeed, has been demonstrated as one of the most important aspects in determining the invasion success of NIS (Ward and Master, 2007). The so-called "invasion window" (Carlton, 1996;Drake et al, 2006;Caplat et al, 2009), depends on the niche availability, i.e., the set of ecological conditions that can transform an invasive species into "the right species at the right moment" (Pranovi et al, 2006). Climatic changes, and in particular ocean warming, are expected to act as a factor contributing to the opening of the invasion window beyond the direct favoring of thermophilic species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Niche availability, indeed, has been demonstrated as one of the most important aspects in determining the invasion success of NIS (Ward and Master, 2007). The so-called "invasion window" (Carlton, 1996;Drake et al, 2006;Caplat et al, 2009), depends on the niche availability, i.e., the set of ecological conditions that can transform an invasive species into "the right species at the right moment" (Pranovi et al, 2006). Climatic changes, and in particular ocean warming, are expected to act as a factor contributing to the opening of the invasion window beyond the direct favoring of thermophilic species.…”
Section: Discussionmentioning
confidence: 99%
“…The poleward shift of thermal habitats makes previously inhospitable areas accessible to more thermophilic (warmer-water) species, and makes the same areas less suitable for the native ones (Walther et al, 2002(Walther et al, , 2009Parmesan, 2006;Bazairi et al, 2010). These two processes are expected to open the so-called "invasion window, " changing an ecosystem's susceptibility to invasion (Carlton, 1996;Drake et al, 2006;Caplat et al, 2009). Climatic changes thus ultimately influence biodiversity (Bianchi and Morri, 2000), increase the risk of extinction for less adaptable species (Bazairi et al, 2010) and affect fisheries (Cheung et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…While Allee effects are reduced due to parthenogenetic reproduction, they may operate during the sexual phase, and thus the overall consequence of Allee effects on establishment remains unknown. In some invaded areas with high boating traffic, Bythotrephes has spread to only roughly 20% of lakes (Weisz and Yan 2010), and it is not clear why this is the case, especially given that a previous study omitting Allee effects (Drake et al 2006) has suggested that even 2 propagules should be sufficient for a 90% probability of establishment. Thus, to estimate the establishment risk, researchers should consider the entire life cycle of the organism, the time spent in each mode of reproduction, and the dynamics affecting each mode.…”
Section: Study Systemmentioning
confidence: 99%
“…With quantified dose-response curves, policy makers could begin to make informed decisions on the benefits of management options that reduce propagule pressure. While several models have evaluated the relationship using parameters from field data for well established populations (Drake et al 2006, Jerde et al 2009), the dynamics early in an invasion need to be assessed, because well established populations have clearly overcome any initial dose-response limitation (i.e., Allee effect thresholds).…”
Section: Introductionmentioning
confidence: 99%
“…The spiny water flea, Bythotrephes longimanus is an invasive species, expanding its range in Eurasia and established in North America (Grigorovich et al 1998, Branstrator et al 2006, Drake et al 2006, where it can be an important element of food webs in lake pelagic zones (Palmer et al 2001). Although it has a wide ecological range, it is most prolific in deeper lakes of low trophy (Palmer et al 2001), such as Lake Ostrowite.…”
Section: Discussionmentioning
confidence: 99%